(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this research was to examine the impact of several nursing treatments on the knowledge of mothers and the nutritional health of children younger than five. The nutritional condition of children improved as a result of some nursing treatments that raised parents’ awareness. Children suffering from severe malnutrition benefited greatly from nutritional supplementation. The study’s aims were to compare the nutritional status of children who had been identified as malnourished before and after receiving selected nursing interventions, to determine whether or not there was a correlation between the mothers’ awareness and the children’s nutritional status, and to determine whether or not the post-test finding was associated with the mothers’ awareness.